If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-3(2v-1)+2(2v+4)=-2v+13
We move all terms to the left:
2-3(2v-1)+2(2v+4)-(-2v+13)=0
We multiply parentheses
-6v+4v-(-2v+13)+3+8+2=0
We get rid of parentheses
-6v+4v+2v-13+3+8+2=0
We add all the numbers together, and all the variables
=0
v=0/1
v=0
| 9z-20=61 | | 3x/8=7/2 | | 3m+5=38 | | 5^x=1 | | h*40+((h*1.5)*4)=961.54 | | 5x-5=7+1 | | 4x^2+3x-36=0 | | 4x^2-3x-36=0 | | 1/5(x-5)=4x-3(x-1)+44/5 | | 7x-2=4x-5= | | 4x/3=11/7 | | 1/6(x+3)=1/5(x-4)=1 | | 13=r/9+8 | | 8x-5.5+4=-26.5 | | 28-1k=7(k-4) | | 12=6x+30 | | -7.2x+3.5=-8.7x-10 | | 31t=72.9 | | p+8/3=-6 | | (x-3)÷4=x÷10 | | 5(a-7)=-25 | | -10x-9=26x-6(6x-9) | | a/5-5=0 | | -4x+-13+-5x=14 | | b-4+6b=35 | | A=16s2+25 | | 24=4x=24 | | H(x)=-2x^2+20x+48 | | 12+2x-12=180 | | 9x^2+5=446 | | -5=6+x/3 | | C+b=16b=6 |